Longitudinal associations between psychological well-being and depressive symptoms among older adults in the Baltic states - Kairys, Antanas; Jurkuvėnas, Vytautas; Skrūzkalne, Iluta; Mikuličiūtė, Vita; Kalniņa, Diāna; Zamalijeva, Olga (Frontiers in Psychology, 2025)
Depression in later life is a pressing public health concern that is often comorbid with chronic illness and associated with substantial declines in psychological well-being. Drawing on the dual continua model of mental health, this study investigated the longitudinal, bidirectional associations between psychological well-being and depressive symptoms among older adults in the Baltic States. Using two waves of data (2019/2020 and 2021/2022) from the Survey of Health, Ageing and Retirement in Europe (SHARE), we analyzed responses from 5,874 individuals aged 50 and above in Estonia, Latvia, and Lithuania. Psychological well-being was assessed using the CASP-12 scale, and depressive symptoms using the EURO-D scale. A cross-lagged panel model, adjusted for age, gender, and multimorbidity, revealed that both constructs were moderately stable over time and negatively associated in each wave. Notably, psychological well-being at baseline significantly predicted depressive symptoms 2 years later (β = −0.17, p < 0.001), and depressive symptoms also predicted subsequent well-being (β = −0.07, p < 0.001), suggesting a bidirectional relationship with stronger effects from well-being to depression. These findings support the dual continua model and underscore the importance of promoting psychological well-being to mitigate depression risk in ageing populations.